Who needs rights? … Reflections on Hellenic critical care patients - Papathanassoglou, Elizabeth; Chrisospathi, Stefania (My University, 2008)
These are some of the responses fromparticipants exploring the issues of pa-tients’ rights in Hellenic critical care units(S. Chrisospathi, University of Athens,Athens, unpublished data). To hear thisextreme sense of passivity from patientsin focus groups was shocking and led usto raise some important questions forhealth care professionals to consider.